Biological Aspects of Charybdis hellerii In The West Tiworo Strait Waters, South Konawe, Southeast Sulawesi - Amrin Amrin; Syamsul Kamri; Abdul Hamid (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The study on the biological aspects of Charybdis hellerii (A. Milne-Edwards, 1867) in the world and Indonesia were very limited. This study aims to measure the sex ratio, gonad development, carapace width and body weight relationship, condition factor, the first size sexual maturity, and fecundity. This study was conducted from July to September 2020 in the western of the Tiworo Strait, South Konawe, SoutheastSulawsei. The C. hellerii samples were bycatch of the blue swimming crab using collapsible traps. The results of sex ratio based on a period show significantly different (p<0,05) with a ratio of 1:1, except Agust. Gonad development males and females dominated mature, while ovigerous females dominated immaturely. The carapace width and body weight relationships between males and females exhibited a strong and positive relationship (r>0,75) with a pattern of growth allometric negative. Condition factor males significantly different (p<0,05) from females and ovigerous females. The first size carapace width sexual maturity male and female respectively were 61,86 mm and 48,90 mm. Fecundity of C. hellerii ranging from 18706 to 506876. These data on biological aspects can contribute to the sustainable management of C. hellerii in the Tiworo Strait.